The concept of pending lawsuit in article 15 of Regulation (EC) no 1346/2000 on insolvency proceedings: annotation on the European Court of Justice Judgment of 6 june 2018, Tarragó da Silveira, Case c-250/17, ecli:eu:c:2018:398 - Lima Pinheiro, Luís de; Gomes de Almeida, João (CUADERNOS DE DERECHO TRANSNACIONAL, 2019)
In the Tarragó da Silveira judgment, the European Court of Justice answers a question referred by the Portuguese Supreme Court of Justice regarding the concept of “lawsuit pending” in article 15 of the Insolvency Regulation. The referring court asks if a debt recovery action is to be considered a pending lawsuit for the purposes of article 15. This case annotation examines and evaluates the solution given by the European Court of Justice.
Keywords: Insolvency Regulation; Regulation No 1346/2000; concept of lawsuit pending